Penerapan Aplikasi Pelayanan Samsat Keliling pada UPTB-UPPD Gerung - Adil, Ahmat; Triwijoyo, Bambang Krismono; Pribadi, Agus; Saputri, Dian Syafitri Chani; Fahly, Moh. Rizky (LPPM Universitas Bumigora, 2023)
Public service is an activity or a series of activities in the context of fulfilling service needs in accordance with statutory regulations. One form of public service that is carried out is the vehicle tax service known as Sistem Administrasi Manunggal Satu Atap (SAMSAT) service. The method used in implementing this application uses 2 stages, namely implementation, and evaluation. At the discussion stage, it contains an explanation as implementation material for the application used. This section contains interfaces in the form of input and output applications. These interfaces are the material for socialization to participants. Besides the interface, this section also discusses the database used. Based on the results of the socialization and evaluation that has been carried out, it is concluded that the implementation of the application is very helpful for officers in carrying out their work.